Tailoring Cardiac Synthetic Transcriptional Modulation Towards Precision Medicine - Schoger, Eric; Lelek, Sara; Panáková, Daniela; Zelarayán, Laura Cecilia (Frontiers in Cardiovascular Medicine, 2022)
Molecular and genetic differences between individual cells within tissues underlie cellular heterogeneities defining organ physiology and function. Up until recently the precise cellular composition of organ systems has been unresolved. With the fast developing field of single cell genomics, we are facing unprecedented leap in information available pertaining organ biology. When applied to diseased tissues, these novel approaches have been immensely improving our understanding of the underlying pathophysiology of common human insults. Simultaneously, the technological advances in CRISPR-mediated regulation of gene transcription, and those more recently applied in the context of epigenome modulation, have opened up novel avenues for targeted therapy and personalized medicine. Here, we discuss the fast-paced advancements of the recent years and the applications thereof in the context of cardiac biology and common cardiac disease. The combination of single cell technologies together with CRISPR-mediated modulation of gene regulatory networks will be instrumental in tailoring the right strategies for each and every patient in the near future.